A population based seroepidemiological survey of Chlamydia pneumoniae infections in schoolchildren. Issue 6 (25th May 2005) - Dal Molin, G; Longo, B; Not, T; Poli, A; Campello, C
Abstract : Aim: A serosurvey was carried out in schoolchildren from a northeastern area of Italy to define the burden of Chlamydia pneumoniae infection. Methods: A sample of 649 schoolchildren underwent a simplified version of the International Study of Asthma and Allergies in Childhood questionnaire and IgG and IgA antibodies were investigated using an enzyme immunoassay, followed by a microimmunofluorescence assay in reactive sera. Results: Of the children examined, 29% and 19.7% had IgG and IgA antibodies, respectively. The IgG prevalence increased with age. No other sociodemographical variable was related to C pneumoniae infection. An association was established between IgA prevalence and previous otitis media. Conclusions: A mesoendemic (intermediate between high and low endemic level) pattern of C pneumoniae infection is present in schoolchildren from this area and the prevalence rate is related to age. Moreover, this is the first epidemiological evidence of the role of C pneumoniae in otitis.